2010
DOI: 10.1007/s11605-010-1282-z
|View full text |Cite
|
Sign up to set email alerts
|

Alternative Port Site Selection (APSS) for Improved Cosmesis in Laparoscopic Surgery

Abstract: The use of laparoscopy can be associated with improved cosmesis following a variety of gastrointestinal procedures versus standard open surgery. The placement of laparoscopic ports in less visible areas of the body such as the bikini line, termed alternative port site selection (APSS), may result in further improved cosmesis. Performance of laparoscopic procedures from such alternative port placement areas may be associated with increased technical challenge. This manuscript discusses APSS approaches for two c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 14 publications
1
4
1
Order By: Relevance
“…These results are in line with other research. 10,15,16,17,19 In contrast to research by, 11,13,19,20 which reported conversion to open surgery, intraoperative challenges, an extra port insertion in the upper abdomen, and long instruments, our study did not find any complications either during the procedure or following it. To reduce the pot size, 5-mm ports could be used in place of the left 10-mm connector.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…These results are in line with other research. 10,15,16,17,19 In contrast to research by, 11,13,19,20 which reported conversion to open surgery, intraoperative challenges, an extra port insertion in the upper abdomen, and long instruments, our study did not find any complications either during the procedure or following it. To reduce the pot size, 5-mm ports could be used in place of the left 10-mm connector.…”
Section: Discussioncontrasting
confidence: 99%
“…In addition, Incisional hernia and wound infection risk have both been linked to SILC. 9,10 In covert laparoscopic cholecystectomy we place the laparoscopic ports in less noticeable body regions, such as the bikini line, is known as alternative port site selection, and it may lead to even better cosmoses. Many Surgeons have expressed interest in doing LC by covert technique through using the modified bikini line method by using one umbilical trocar and three trocars implanted along the suprapubic line because it has many benefit as it hidden scar or reduced scar , lower costs, and the ability to apply the same laparoscopic principles as standard.…”
Section: Introductionmentioning
confidence: 99%
“…There was no need for any additional ports or long instruments. These findings are consistent with earlier research [8,10,13,14]. Other investigations [6,12,[15][16][17], on the other hand, conversion to open surgery, intraoperative complications, an extra port insertion in the upper abdomen, and long instruments were reported.…”
Section: Discussionsupporting
confidence: 92%
“…This correlates with other reports. In addition, several recent studies showed that SA leads to less postoperative pain compared to CA [ 10 , 11 , 23 , 26 , 27 ].…”
Section: Discussionmentioning
confidence: 99%